2011
DOI: 10.1002/asna.201111538
|View full text |Cite
|
Sign up to set email alerts
|

GRB 021004 host galaxy and environment with X‐shooter

Abstract: International audienceWe report preliminary results of the observation of the GRB 021004 host galaxy and field obtained with the new VLT/X-shooter spectrograph. Thanks to the X-shooter wide spectral range we could detect many emission lines associated to the GRB host at z=2.33102. Moreover we identify [O III] λλ 4959, 5007 Å emission lines at z=2.33184 associated with a close-by galaxy possibly interacting with the GRB host. We do not detect any counterpart of the foreground absorbers found in the afterglow sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The X-shooter observation of the host galaxy (Prog. ID: 084.A-0631; PI: S. Piranomonte, see Table 2) has previously been published in Vergani et al (2011). In Fig.…”
Section: Grb 021004mentioning
confidence: 99%
See 2 more Smart Citations
“…The X-shooter observation of the host galaxy (Prog. ID: 084.A-0631; PI: S. Piranomonte, see Table 2) has previously been published in Vergani et al (2011). In Fig.…”
Section: Grb 021004mentioning
confidence: 99%
“…7 we show the image of GRB 021004 field with the slits used to observe the host galaxy and the afterglow superimposed. Vergani et al (2011) reported the detection of the [OIII]λ5007 emission line at the same redshift as the GRB from the galaxy eastward of the GRB host in the spectrum obtained with the slit position angle PA = 92 • . Its proximity to the GRB host (projected distance of 14 kpc) may indicate a possible interaction between this galaxy and the GRB host.…”
Section: Grb 021004mentioning
confidence: 99%
See 1 more Smart Citation
“…7, we show the image of GRB 021004 field with superimposed the slits used to observe the host galaxy and the afterglow. Vergani et al (2011) report the detection of [OIII]λ5007 emission line, at the same redshift as the GRB, from the galaxy eastward of the GRB host in the spectrum obtained with the slit position angle PA=92 • . Its proximity to the GRB host (projected distance of 14 kpc) may indicate a possible interaction between this galaxy and the GRB host.…”
Section: Grb 021004mentioning
confidence: 99%
“…Once the afterglow has faded, the host galaxy can be directly observed through photometry and spectroscopy. This offers the interesting possibility of combining information on the cold and warm gas with the emission properties of the GRB host galaxy (e.g., Vergani et al 2011;Chen 2012;Friis et al 2015;Wiseman et al 2017;Arabsalmani et al 2018).…”
Section: Introductionmentioning
confidence: 99%